Application of heating on the antioxidant and antibacterial properties of Malaysian and Australian stingless bee honey - Mat Ramlan, Nurul Ainaa Farhanah; Md Zin, Aina Syahirah; Safari, Nur Fatihah; Chan, Kim Wei; Zawawi, Norhasnida (Multidisciplinary Digital Publishing Institute, 2021)
In the honey industry, heat treatments are usually applied to maintain honey’s quality and shelf life. Heat treatment is used to avoid crystallisation and allow the easy use of honey, but treatment with heat might affect the antioxidant and antibacterial activities, which are the immediate health effects of honey. This study will determine the effect of heat treatment on Malaysian and Australian stingless bee honey (SBH) produced by the common bee species in both countries. Eighteen honey samples were subjected to heat at 45 °C, 55 °C and 65 °C for one hour and subsequently analysed for their total phenolic content (TPC), total flavonoid content (TFC), DPPH radical scavenging activity, ferric reducing antioxidant power (FRAP) and minimum inhibitory concentration (MIC). The results show that all samples had high TPC, TFC and antioxidant activities before the treatment. The heat treatments did not affect (p < 0.05) the TPC, TFC and antioxidant activities in most samples, but did inhibit the antibacterial activities consistently in most of the samples, regardless of the bee species and country of origin. This study also confirms a strong correlation between TPC and TFC with FRAP activities for the non-heated and heated honey samples (p < 0.05). Other heat-sensitive bioactive compounds in SBH should be measured to control the antibacterial properties present.